OPTIMALISASI MANAJEMEN STRATEGI DALAM MENINGKATKAN KINERJA PELAKU BISNIS UKM PADA ERA EKONOMI DIGITAL - Yusuf (Nusantara Hasana Journal, 2023)
The Covid-19 pandemic has had a major impact on the development of Micro, Small and Medium Enterprises (MSMEs). MSMEs must find the right strategy to survive. One of the strategies during the pandemic is digital marketing which allows MSME actors to market their products without being constrained by policies during the pandemic. Research on digital marketing strategies for MSMEs to compete in this pandemic era uses qualitative methods with a descriptive analysis approach. Descriptive research is collecting data based on the factors that support the object of research. Qualitative research deals with ideas, perceptions, opinions, beliefs of the people to be studied and all of them cannot be measured by numbers. The purpose of the study was to find out how the techniques, elements, processes and activities of MSME actors in using digital marketing to compete during the pandemic. The results show that there are still a few MSMEs that use digital marketing (15.08%) as a strategy to increase sales and require an understanding of digital marketing. Based on research analysis, MSMEs that already use digital marketing are able to survive and even increase sales without relying on conventional stores.